High Melting Point of Linear, Spiral Polyethylene Nanofibers and Polyethylene Microspheres Obtained Through Confined Polymerization by a PPM‐Supported Ziegler‐Natta Catalyst - Dr. Yu Xiao; Dr. Xiying Dai; Dr. Kui Wang; Prof. Guangyuan Zhou (ChemistryOpen, 2020)
Abstract In this work, different types of polyethylene (linear, spiral nanofibers and microspheres) were obtained via confined polymerization by a PPM‐supported Ziegler‐Natta catalyst. Firstly, the Ziegler‐Natta catalyst was chemical bonded inside the porous polymer microspheres (PPMs) supports with different pore diameter and supports size through chemical reaction. Then slightly and highly confined polymerization occurred in the PPM‐supported Ziegler‐Natta catalysts. SEM results illustrated that the slightly confined polymerization was easy to obtain linear and spiral nanofibers, and the nanofibers were observed in polyethylene catalyzed by PPMs‐1#/cat and PPMs‐2#/cat with low pore diameter (about 23 nm). Furthermore, the highly confined polymerization produced polyethylene microspheres, which obtained through other PPM‐supported Ziegler‐Natta catalysts with high pore diameter. In addition, high second melting point (Tm2: up to 143.3 °C) is a unique property of the polyethylene obtained by the PPM‐supported Ziegler‐Natta catalyst after removing the residue through physical treatment. The high Tm2 was ascribed to low surface free energy (σe), which was owing to the entanglement of polyethylene polymerized in the PPMs supports with interconnected multi‐modal pore structure.